Frequency agile microstrippatch antenna - Sharma S.K.; Vishvakarma B.R. (My University, 2025)
A rectangular patch loaded with shorting posts as well as varactor diodes was investigated theoretically using a Modal Expansion Cavity Model, with a view to predicting the obtainable tuning range and its effect on the radiation characteristics of theantenna. The tuning range in the shorting-posts loaded patch was found to be 450 MHz, which is almost double the earlier reported data, whereas in the varactor-loaded patch it was almost the sameas reported range. The results obtained from the proposed method are in good agreement with the previously reported one. © 1998 Taylor and Francis Group, LLC.